SYNTHESIS OF NANOFIBRE AND SILVER NANOPARTICLES FROM COELOMIC FLUID OF EARTHWORM, EUDRILUS EUGENIAE AND PONTOSCOLEX CORETHRURUS AND ITS ANTIMICROBIAL POTENCY - LEKSHMI N.C.J, PACKIA; S, VIVEKA; Kumari R, Sahila; Bharath M, Selva; S, Jeeva; J, Rajabrindha; K, Vaikundaraj; Kumar P, Dinesh (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Nanotechnology is also referred to the ability for designing, characterization, production and application of structures. An increasingly common application is the use of silver nanoparticles and nanofibers for antimicrobial coatings, wound dressings, and biomedical devices. In this recent world earthworms are showing the excellent scale in the medical field. In this present paper we have collected Eudrilus eugeniae, and Pontoscolex corethrurus to harvest the coelomic fluid from the earthworm for the synthesis of silver nanopaticles and nanofibers. Nanofibers are synthesized using human collagen and poly lactic acid. Coelomic fluid and Ag NPS was investigated for antibacterial activity and haemolytic activity. Haemolytic activity of Eudrilus eugeniae was observed even in low quantity of coelomic fluid and haemolysis was observed for Pontoscolex corethrurus only in high quantity of fluid. The antimicrobial activity was found high in all types of earthworms. But nanoparticles from coelomic fluid showed higher activity than the coelomic fluid. Nanofibres from coelomic fluid does not showed any bioactivity against pathogens. Ag NPS was confirmed by the colour reduced to form brown and by UV-visible spectrum in the range of 400 to 430nm. Protein profile was investigated by the SDS-PAGE and the molecular weight was determined as 200KDa. From this study we conclude that the coelomic fluid from earthworm can be used as therapeutic agent. Keyword: Ag NPS, Nanofibers, Haemolysis, UV-visible spectrum, SDS-PAGE